2011
DOI: 10.1016/j.pharmthera.2011.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny and regulation of the serotonin transporter: Providing insights into human disorders

Abstract: Serotonin (5-hydroxytryptamine, 5-HT) was one of the first neurotransmitters for which a role in development was identified. Pharmacological and gene knockout studies have revealed a critical role for 5-HT in numerous processes, including cell division, neuronal migration, differentiation and synaptogenesis. An excess in brain 5-HT appears to be mechanistically linked to abnormal brain development, which in turn is associated with neurological disorders. Ambient levels of 5-HT are controlled by a vast orchestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 357 publications
(456 reference statements)
0
100
0
Order By: Relevance
“…The complexity of Sert expression and function is not yet fully understood (Daws & Gould, 2011). Nonetheless, given that in vitro studies have shown that long-term exposure to high glucose concentrations further increases the activity of Sert (Goncalves et al, 2008), it is possible that the consumption of refined carbohydrate over an extended time determined the patterns of expression of Sert seen in our investigation.…”
Section: Discussionmentioning
confidence: 85%
“…The complexity of Sert expression and function is not yet fully understood (Daws & Gould, 2011). Nonetheless, given that in vitro studies have shown that long-term exposure to high glucose concentrations further increases the activity of Sert (Goncalves et al, 2008), it is possible that the consumption of refined carbohydrate over an extended time determined the patterns of expression of Sert seen in our investigation.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, for several of these variants, their activity cannot be further increased by p38 MAPK activation , suggesting these variants may be constitutively poised in the state normally produced after p38 MAPK activation. Expression of SERT molecules with constitutively elevated 5-HT clearance could drive developmental onset disorders linked to 5-HT such as ASD owing to the early embryonic expression of 5-HT and SERT (Daws and Gould, 2011). Recently, a mouse with a knock-in mutation of the most common of these variants, Ala56, was generated and found to exhibit behavioral perturbations reminiscent of ASD .…”
Section: Regulation Of Serotonin Transporter By P38 Mitogen-activamentioning
confidence: 99%
“…This mechanism results in the inactivation of 5-HT by removing it from the synaptic cleft. Studies have also shown that a 5-HT reuptake inhibitor (SRI) interferes with SERT function to inhibit or suppress 5-HT reuptake [80,81].…”
Section: Serotonin -A Chemical Messenger Between All Types Of Living mentioning
confidence: 99%